PEMBERDAYAAN PENGRAJIN BAMBU SABUK SEMERU DI DESA SUMBERMUJUR KECAMATAN CANDIPURO KABUPATEN LUMAJANG PROVINSI JAWA TIMUR - Hasminanda Yuniasari; Juliati Prihatini; Syaefulloh Syaefulloh (ipdn, 2021)
Bamboo handicrafts in Sumbermujur Village use bamboo waste, but the quality of this handicraft product is quite good. The problem that arises is when there is a lot of production but it is difficult to access marketing, plus there is no capital assistance, so bamboo craftsmen need to be empowered. This research was conducted from January 5, 2021 to February 5, 2021. The purpose of this study was to empower bamboo craftsmen in Sumbermujur village, the inhibiting factors and efforts to overcome the inhibiting factors. The research method used is descriptive qualitative. Data collection techniques through observation, interviews and documentation. Technical analysis of data is carried out through Human Development, Business Development, Environmental Development and Institutional Development. The results show that of the four development programs, three of them are good, namely human development, environmental development and institutional development. While business development still needs to be improved, this is because the quality of products from bamboo craftsmen in Sumbermujur Village must compete with other bamboo craftsmen's products that already have a market share. The recommendation of this research is the need for government facilitation through the Department of Tourism and Culture to find work partners to be able to access market share. In addition, the agency must provide capital facilitation in the form of soft loans. Keywords: bamboo craftsmen, community empowerment, tourism village